How Zero Can Become Equal to One

Next Science Page

Previous Science Page

Back to index

 

First of all, the following determinant’s value is zero.

| 0 1 0 |

| 1 0 1 |

|0 1 0 |

= 0 | 0 1 |    - 1 | 1 1 | + 0 | 1 0 |

       | 1 0 |          | 0 0 |       | 0 1 |

= 0 – 0 + 0

= 0

Normally,

0 * 0 =1

But if we realize that one equation is repeated, we can get an interesting and happy coincidence.

The square matrix  becomes a rectangular one.

[101]

[010]

If we repeat the first row, we get a five on a die, or the stereographic projection for mm2.

[101]

[010]

[101]

If we manipulate the set of two rows, we can get some interesting comparisons to real results for the atomic triple of the proton, neutron, and electron.

First of all:

|101|

|010|

|101|

= 1*|10|

|01|

-          0*|00|

|11|

+1*|01|

|10|

=1-0-1

=0

= independence condition

|101|

|010|

=0

Placeholders of |p n e| for proton, neutron, and electron.

|101|=|p n e|=0

Or:

P+e=0=n

P=-e

Which corresponds to the charge condition for the proton and electron.

Note:

[101]

[101]

Really is:

[202]

2p +2e=0=n

Or:

2p=n

Or similarly:

[010]

[010]

n+n=0=2n=[chargeless condition of zero]

or:

2p +2n

Or the [4,2] series of [2n+2p, 2p]

Similarly,

[101]

[010]

Corresponds to the [2,1] series of [n+p,p].

Note that if we assume that

[101]

And

[010]

Are points, then these can define a straight line from:

[ x y z ] points of [1,0,1] and [0,1,0] or the corresponding vector.

(1-0,0-1,1-0)

=(1,-1,1)

=(p+,e-,no)

{note:   the position of the  placeholders changes slightly}

So that:

0*0 can become a straight line

{or a “vibrating string”, quantum mechanically }

So that:

0*0 <>0 and from the above derivation, probably “one” in some form or other.